(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
A newly opened excavation in the Cassina beds of the Lower Meride Limestone (Monte San Giorgio UNESCO WHL, Canton Ticino, Southern Alps) has yielded a small collection of Ladinian plant fossils, together with vertebrate (mostly fish) and invertebrate remains. The flora contains at least five species; conifer remains assignable to the genera Elatocladus, Voltzia and ?Pelourdea are the most common elements. A new species, Elatocladus cassinae n. sp., is formally described. Co-occurring with the conifers are seed ferns (Ptilozamites) and a few putative cycadalean remains (?Taeniopteris). Among the identified genera, only Voltzia has previously been reported from Monte San Giorgio. The fossils presented in this paper indicate that a diversified flora thrived in the region during the Ladinian. Floral composition and preservation patterns are suggestive of a taphonomically-biased record and a relatively far-away source area.